2017
DOI: 10.1093/cid/cix290
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Disease and Pregnancy: A Retrospective Cohort Study of Patients Managed at 5 Ebola Treatment Units in West Africa

Abstract: SummaryWe find no evidence to support a difference in the risk of death among pregnant women with suspected or confirmed Ebola virus disease (EVD) as compared to nonpregnant women. Limited data suggest poor fetal and neonatal outcomes in EVD-affected pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Overall CFR is high (45-90%) and if acquired in pregnancy it is almost always lethal for the fetus (213,215). However, a recent synthesis of available studies demonstrated no significant difference between mortality rates in pregnant vs. non-pregnant women (214). While this may be the case, caution is required on two counts: firstly, as the authors acknowledge, their analysis is limited by the small size, retrospective nature and considerable heterogeneity of included studies; and secondly, while pregnant women may not be intrinsically more vulnerable to EVD, the fact that they are often carers for sick relatives and make frequent visits to health facilities places them at increased risk of acquiring the disease (212).…”
Section: Ebola Virusmentioning
confidence: 99%
“…Overall CFR is high (45-90%) and if acquired in pregnancy it is almost always lethal for the fetus (213,215). However, a recent synthesis of available studies demonstrated no significant difference between mortality rates in pregnant vs. non-pregnant women (214). While this may be the case, caution is required on two counts: firstly, as the authors acknowledge, their analysis is limited by the small size, retrospective nature and considerable heterogeneity of included studies; and secondly, while pregnant women may not be intrinsically more vulnerable to EVD, the fact that they are often carers for sick relatives and make frequent visits to health facilities places them at increased risk of acquiring the disease (212).…”
Section: Ebola Virusmentioning
confidence: 99%
“…The World Health Organization's Strategic Advisory Group of Experts on Immunization, recognizing the high risk for maternal and fetal death from Ebola virus infection, has endorsed the need for careful evaluation of risks and benefits in a local context by national regulatory authorities and ethics committees in decisionmaking about rVSVΔG-ZEBOV-GP vaccination of pregnant women during an Ebola outbreak (27). The decision to offer rVSVΔG-ZEBOV-GP vaccine to pregnant women will need to balance the risk for an adverse pregnancy outcome with the risk for exposure to and subsequent infection with Ebola (28)(29)(30)(31)(32)(33). When vaccination is offered to pregnant women, the provision of culturally appropriate information to assist women in making informed decisions about whether to accept vaccination will be critical.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a retrospective evaluation of outcome data from the West African epidemic, the authors found no evidence to support a significant difference in CFRs between pregnant women with suspected or confirmed EVD compared to non-pregnant women [34].…”
Section: Mortality Of Ebola Virus Infection Among Non-vaccinated Pregmentioning
confidence: 98%